Engineering Novel 3D Models to Recreate High‐Grade Osteosarcoma and its Immune and Extracellular Matrix Microenvironment. Issue 19 (4th September 2022) - Pierrevelcin, Marina; Flacher, Vincent; Mueller, Christopher G.; Vauchelles, Romain; Guerin, Eric; Lhermitte, Benoît; Pencreach, Erwan; Reisch, Andreas; Muller, Quentin; Doumard, Layal; Boufenghour, Wacym; Klymchenko, Andrey S.; et al.
Abstract: Osteosarcoma (OS) is the most common primary bone cancer, where the overall 5‐year surviving rate is below 20% in resistant forms. Accelerating cures for those poor outcome patients remains a challenge. Nevertheless, several studies of agents targeting abnormal cancerous pathways have yielded disappointing results when translated into clinic because of the lack of accurate OS preclinical modeling. So, any effort to design preclinical drug testing may consider all inter‐, intra‐, and extra‐tumoral heterogeneities throughout models mimicking extracellular and immune microenvironment. Therefore, the bioengineering of patient‐derived models reproducing the OS heterogeneity, the interaction with tumor‐associated macrophages (TAMs), and the modulation of oxygen concentrations additionally to recreation of bone scaffold is proposed here. Eight 2D preclinical models mimicking several OS clinical situations and their TAMs in hypoxic conditions are developed first and, subsequently, the paired 3D models faithfully preserving histological and biological characteristics are generated. It is possible to shape reproducibly M2‐like macrophages cultured with all OS patient‐derived cell lines in both dimensions. The final 3D models pooling all heterogeneity features are providing accurate proliferation and migration data to understand the mechanisms involved in OS and immune cells/biomatrix interactions and sustained such that engineered 3D preclinical systems will improve personalized medicine. Abstract : Accelerating cures for osteosarcoma (OS) poor outcome patients remain a challenge. So, there is an urgent need to develop relevant preclinical 2D and 3D modelization able to mirror pathophysiologically cell‐to‐cell interactions impacting OS cell behavior and engineer extrinsic heterogeneity able to modulate response to therapies like the bone extrinsic mechanical properties, which are taking part to OS development.